O exercício e a construção do ensino da metodologia de investigação científica em saúde coletiva Building up and practicing the teaching of the scientific research methodology in collective health - Hisako Shima; Maria Josefina Leuba Salum; Vilma Machado de Queiroz (SciELO, 1996)
Os autores apresentam e discutem a operacionalização de uma disciplina de Metodologia de Investigação Científica em Saúde Coletiva, ministrada para alunos da Area de Concentração de Enfermagem em Saúde Coletiva do Programa de Pós-Graduação em Enfermagem da USP, cujo desenvolvimento foi norteado pelo referencial do materialismo histórico e dialético. The authors present and discuss the development of a discipline of Scientific Research Methodology in Public Health, taught to students of The Nursing Concentration Area in Public Health - from the Nursing Graduation Program of São Paulo University. The discipline was based in the framework of the historical and dialectical materialism.